2013
DOI: 10.1002/phar.1365
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Inhaled Nitric Oxide and Aerosolized Epoprostenol in Acute Lung Injury or Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome (ARDS) and acute lung injury (ALI) are conditions associated with an estimated mortality of 40–50%. The use of inhaled vasodilators can help to improve oxygenation without hemodynamic effects. This article reviews relevant studies addressing the safety and efficacy of inhaled nitric oxide (iNO) and aerosolized epoprostenol (aEPO) in the treatment of life-threatening hypoxemia associated with ARDS and ALI. In addition, the article also provides a practicable guide to the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 61 publications
(116 reference statements)
0
83
0
Order By: Relevance
“…In addition, as previously discussed, the mortality rate observed in this study was significantly higher than those reported in previous literature. 8,10,29 It is unlikely that the high mortality rate is associated with disparities in the clinical management of severe ARDS since the ventilatory parameters were consistent with those described in recent guidelines. 30 Hence, the high mortality is most likely a reflection of the severity of illness when inhaled vasodilators are considered in patients with severe ARDS.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, as previously discussed, the mortality rate observed in this study was significantly higher than those reported in previous literature. 8,10,29 It is unlikely that the high mortality rate is associated with disparities in the clinical management of severe ARDS since the ventilatory parameters were consistent with those described in recent guidelines. 30 Hence, the high mortality is most likely a reflection of the severity of illness when inhaled vasodilators are considered in patients with severe ARDS.…”
Section: Discussionmentioning
confidence: 70%
“…Patients who received iVEL had shorter durations of mechanical ventilation (5 [2-7] vs 9.5 [6][7][8][9][10][11][12][13][14][15][16][17][18][19] days, P < 0.001) and ICU LOSs (7 [5][6][7][8][9][10][11][12] vs 15.5 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] days, P < 0.001) compared with patients who received iFLO. There was no difference in hospital LOS or duration of inhaled epoprostenol therapy when comparing groups.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the role of inhaled nitric oxide for alleviation of ARDS and altering renal function has to be defined, including its anti-inflammatory properties (15). Several favorable effects are known, although trials and meta-analyses have failed to demonstrate its beneficial use in ARDS (16). Inhaled nitric oxide causes selective vasodilation of pulmonary vessels in ventilated areas without affecting systemic blood pressure and cardiac output, improves ventilationperfusion mismatch, and is a valuable option to reduce PH in susceptible patients (17).…”
mentioning
confidence: 99%